Pelayanan Kesehatan Pimer : Suatu Penilaian Sosial dari Sudut Pandang Antropologi Kesehatan - Nico Kalangie (Antropologi Indonesia, 1999)
The failure of many social development programs, such as health improvement programs, is a common reality in developing countries. The author argues that the main source of the problems lies on government organizations as the agent for development. Through an examination of a number of models on the introduction of health care, the author shows that the ethnocentrism of health professionals with regard to the communication of innovations remains a problem. What is needed is a communication strategy that is culturally aware, that will allow for the adoption of new ideas and practices through a learning process that is in accord with the principles of the culture participations. That any adoption will be adopted and integrated with the cultural elements of the participants should be taken as a matter of course.